ダイ40ジ ナンキョク チイキ カンソクタイ エットウ タイイン ノ ケンコウ ジョウキョウ - 大谷, 眞二; オオタニ, シンジ; 草谷, 洋光; クサガヤ, ヒロミツ; Otani, Shinji; Kusagaya, Hiromitsu (2002)
P(論文) 第40次南極地域観測隊越冬隊員の健康状態を検討した。対象は40人(うち女性1人)で, 越冬期間中(1999年2月∿2000年1月)に体重, 体脂肪率, 血液一般・生化学検査を行った。その結果, 体脂肪率, トリグリセリド, カルシウム, γ-GTPは越冬開始期と比較して越冬期間中に有意に増加した。AST(GOT), クレアチニンキナーゼ(CK)は越冬初期で高値であり, とくにCKは異常高値であった。赤血球数や血色素量はほとんど変化せず, 白血球数, 血小板数は越冬中に低下した。過去の越冬隊と比較して40次越冬中の隊員の栄養状態は悪くなく, むしろ過多傾向であることが示唆された。また, 越冬初期のASTおよびCKの高値は, 基地作業による高度の筋肉疲労が反映されているものと考えられた。越冬中の白血球数, 血小板数の低下には免疫系の関与が推測されており, 今後, 検討されるべき課題である。 A health survey of members of the 40th Japanese Antarctic Research Expedition was conducted. The subjects were 39 males and 1 female who underwent serial examinations for physical, hematological and sero-biochemical analyses, periodically, during the winter period between February 1999 and January 2000. Percent body fat mass and serum levels for triglyceride, calcium, and γ-glutamyl transpeptidase increased significantly, compared to initial levels, during the wintering period. Further, at the start of the wintering period, significantly increased values were observed in levels of both serum aspartate aminotransferase (AST) and creatine kinase (CK). There were no great changes in the number of red blood cells and hemoglobin; however, decreases in the number of white blood cells (WBC) and platelets were observed during this period. No deterioration in nutritional parameters during this period was observed in this party. Initial increases of AST and CK seemed to be induced by muscle fatigue due to over-work in repair and re-construction of the wintering station. Careful consideration should be paid to the difference in order to clarify the association between the reduction in the number of WBC and platelets, and impaired immunocompetence. departmental bulletin paper